The impact of public responses toward healthcare workers on their work engagement and well-being during the Covid-19 pandemic - Shan, Wen; Wang, Zhengkui; Su, Millie Yun (Frontiers in Psychology, 2022)
Introduction/context: Healthcare workers (HCWs) play an important role in fighting against the COVID-19 pandemic. However, they have been exposed to mixed public responses more significantly during the COVID-19 pandemic, which have potentially affected their work and life. Aim: We aim to study what public responses towards HCWs existed, how and why such public responses impacted HCW’s work engagement and well-being, and how Human Resource (HR) professionals navigate these impacts. These understandings are important for improving HCWs’ work and life quality. Methods: We adopted a mixed approach including both quantitative and qualitative methods to investigate how the public responses impact HCWs’ work engagement and well-being and how human resource management (HRM) shall intervene. Our quantitative study enables us to collect and analyze a large amount of public responses towards HCWs from the social media platform during the COVID-19 pandemic globally, and uncover the sentiments and topics of these pubic responses via big data and AI technologies. Our qualitative study allows us to understand how and why these public responses impact HCWs’ work engagement and well-being via interviews and further identify how HR professionals shall navigate these impacts. Results: The sentiment analysis showed that 55.9% of the discussions toward HCWs were positive, 27.2% were neutral, and 16.9% were negative. The topic modeling analysis indicated that the commonly identified topics were related to fear (the negative responses) and gratitude (the positive responses). The interviews revealed that HCWs’ work engagement and well-being were decreased by negative public responses through experiencing tension or disappointment due to social and physical ostracism, rejection, discrimination, and criticism. On the other hand, positive public responses in terms of encouragement, recognition, and tangible donations increased their work engagement and well-being. The analysis also suggested that occupational calling served as a mechanism that explained why public responses had such impacts on HCWs. The interview results also highlighted the significance of HRM in bridging positive public responses toward HCWs and revealed problems with communication from HRM during the pandemic. This research provides practical implications about how to improve HCWs work-engagement and well-being during the pandemic via public and HRM efforts.